Interactions between frugivorous bats (Chiroptera: Phyllostomidae) and Piper tuberculatum (Piperaceae) in a tropical dry forest in Valle del Cauca, Colombia - Montoya-Bustamante, Sebastián (2016)
In any ecosystem, fruits are resources that vary in time and space as well as in nutritional content. Coexistence of species from a trophic guild depends on the division and use of resources. Therefore, the organisms that depend on them as a food source, tend to show a certain degree of specialization. This way, understanding the factors that influence the dynamics of seed dispersal is important for the regeneration and conservation of tropical ecosystems. Our aim was to determine variation in consumption of Piper tuberculatum by fruit bat assemblages in the village of Robles (Jamundí, Valle del Cauca, Colombia). P. tuberculatum is a resource used not only by wildlife but also by people in the village of Robles. Bats were captured in mist nets between June and November 2014, their feces were collected, and the length of the forearm, wing area, leg length and mass were recorded. At the Universidad del Valle seed laboratory, fecal samples were washed, and their content determined. Of the 14 species captured, Sturnira lilium, Carollia brevicauda, Carollia perspicillata and Artibeus lituratus showed signs of having consumed P. tuberculatum. Sturnira lilium was the main consumer of P. tuberculatum fruits, with the greatest number of consumption events of fruit from this plant species, whereas the other bats showed more diversified consumption events. The greatest niche overlap was recorded between C. brevicauda and C. perspicillata, species that showed similar sizes (i.e., wing area and forearm length) followed by S. lilium and C. perspicillata. In contrast, A. lituratus showed the least niche overlap with the other three fruit bats captured. In conclusion, Sturnira lilium showed an interaction Sturnira-Piper, which is the result of low Solanum availability, and this bat species was the largest consumer of P. tuberculatum in the region.